The Norwegian Natural Ice Industry and Ice Exporter Thomas Johannes Wiborg (1870–1930) - Knut M. Nygaard (Cappelen Damm Akademisk/NOASP, 2023)
This book is about the development of the Norwegian natural ice industry in the period 1870 to 1930, with a particular focus on one of Norway's largest ice exporters, Thomas Johannes Wiborg (1845–1929). In addition to roughly 60 years in the ice industry, Wiborg was also active in international shipping as charterer and, from 1915, a shipowner. The book discusses the growth and decline of the Norwegian natural ice industry, changes in the international market for ice, and the general relationship between ice exports and the shipping sector. How T. J. Wiborg managed to survive for so long in an industry where volumes and values changed almost from year to year, is a key issue explored in the book. The Norwegian Natural Ice Industry and Ice Exporter Thomas Johannes Wiborg (1870–1930) will appeal to academic specialists with interests in biographies, ice, shipping, technological and economic history and development, as well as the general reader.
Keywords: 330; ice export; shipping; market conditions; internationalisation; innovation; shipowning